2002
DOI: 10.1093/annonc/mdf270
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment serum levels of matrix metalloproteinase-9 and vascular endothelial growth factor in non-small-cell lung cancer

Abstract: Future studies may support our hypothesis that the pretreatment serum level of MMP-9 is a new powerful prognostic marker and can help to stratify NSCLC patients with stage I/II disease into low- and high-risk groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

11
54
2
5

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(72 citation statements)
references
References 29 publications
11
54
2
5
Order By: Relevance
“…In agreement with previous studies (Laack et al, 2002;Chakra et al, 2008). we found that a high serum VEGF level did not independently determine prognosis of lung cancer.But several other studies produced conflicting results (Kaya et al, 2004;Hasegawa et al, 2005).…”
Section: Discussionsupporting
confidence: 93%
“…In agreement with previous studies (Laack et al, 2002;Chakra et al, 2008). we found that a high serum VEGF level did not independently determine prognosis of lung cancer.But several other studies produced conflicting results (Kaya et al, 2004;Hasegawa et al, 2005).…”
Section: Discussionsupporting
confidence: 93%
“…22 There are, however, few previous publications report that serum MMP-9 would have any prognostic role in cancer patients. [15][16][17][18] The prognosis of squamous cell carcinoma of head and neck is traditionally linked to the TNM stage, differentiation (grade) and performance status. However, these factors are not sufficient enough to predict outcome accurately.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13][14] Recently, increased serum MMP-9 and MMP-2 levels have been reported to be practical in predicting disease prognosis in some types of tumors. [15][16][17][18] Several studies have shown that gelatinases are expressed in head and neck carcinoma cells, and gelatinases may take part in the progression and invasion of these tumors. [19][20][21] We have recently found that MMP-9 positivity in immunohistochemical staining is associated with unfavorable prognosis in head and neck squamous cell carcinoma.…”
mentioning
confidence: 99%
“…In comparison with healthy controls, the serum levels of MMP-9 are elevated in head and neck squamous cell carcinoma (23,24) and in colon (25), gastric (26), bladder, breast, and prostate cancer (27). Furthermore, elevated MMP-9 serum levels have been shown to correlate with poor survival in stage I to II non -small cell lung cancer patients (28).…”
mentioning
confidence: 99%